O código de defesa dos usuários dos serviços públicos : análise da efetividade no estado de Sergipe e dos desafios e oportunidades do novo normal - Nascimento, Vinícius de Souza (2021)
The Law 13,460, from June 26, 2017, known as the Defense Code for Users of Public Services, represented a remarkable advance in the protection of the basic rights of the target audience of public services, bringing essential innovations in ensuring participation, in defendding the rights of those who interact with the State and in the search for an adequate provision of services, such as: charter of services to the user, council of the users of public services, continuous evaluation of public services, manifestation channel in the ombudsman and annual management report of the ombudsman. The present study was then conducted with the purpose of analyzing how 32 (thirty-two) of the 76 (seventy-six) executive powers existing in Sergipe are complying with the guidelines of the Public Services User Defense Code. For this purpose, it was estabilshed the specific objective of verifying, among the executive powers of the state of Sergipe, the existence of a Regulatory Standard of the Law 13,460/2017, the functioning of the institutes conceived by the said law and the remaining obstacles for its implementation. The theoretical reference was outlined by the analysis of themes linked to citizenship and social participation, to studies related of the Law 13,460/2017 and to the challenges and expectations of the new normal in Public Administration, which deals with the difficulties and opportunities linked to the context of pandemic and development of digital public administration. In methodological terms, through a qualitative approach and with a primarily exploratory nature, the goal was to determine the performance of the executive powers in complying with the applicable legislation, with no prejudice from the explanatory bias, which aimed to identify factors that might be hindering such effectiveness. Thus, a single case study strategy with multiple data sources was used, through questionnaires sent to municipal governments that had re-elected managers and Sergipe’s State Government, in addition to document analysis and, exceptionally, consultations on institutional websites. The results showed worrying data, such as the lack of local coverage of the legislation among the executive powers that responded to the aforementioned questionnaire, in addition to information that demonstrated the precarious or non-existent functioning of most innovations conceived by the CDUSP. On that occasion, the remaining objectives for the implementation and effectiveness of the legislation in question were also verified. In view of the forementioned obstacles and, mainly, of the relevant constitutional competences of Sergipe´s State Court of Auditors, then, the intervention proposal was formatted in the form of an action plan, with a set of referral proposals, delimited as to the focuses , objectives, methodologies and agencies or sectors, aimming to enable the full implementation of the guidelines contained in the Code of Defense of Public Services Users between the jurisdictional administrative units of the Sergipe´s Court of Auditors.